Komunikasi Efektif Dalam Supervisi Pendidikan - Moh Suhri Rohmansyah; Agus Gunawan; Enung Nugraha (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This article discusses the important role of communication in the context of educational supervision. Effective communication between supervisors and educators is the main foundation in improving the quality of teaching and learning in educational institutions. Through the analysis of the concept of supervision and communication theory, this article explores the dynamics of interaction between supervisors and educators, as well as its impact on teacher professional development and improving the quality of education. Deep understanding of interpersonal communication, constructive feedback, and communication strategies that support learning are key focuses in exploring the positive potential of educational supervision. The research method used is a literature review research method, this method was chosen to further examine how communication in educational supervision. From this research, it was found that a leader and subordinate to be able to open communication effectively and efficiently so that the wheels of the organization can run smoothly in achieving predetermined goals.